The effect of macroeconomics variables to Net Asset Value (NAV) growth of sharia mutual funds in Indonesia - Intan Aulia Ardhani; Jaenal Effendi; Mohammad Iqbal Irfany (Jurnal Ekonomi dan Keuangan Islam, 2020)
Purpose – This study aims to perform the short-term and long-term relationships between net asset value of Islamic mutual funds within macroeconomic variables, to analyze responses towards the economic shock, and to analyze the composition of the net asset value of Islamic mutual funds within selected macroeconomic variables.